Occupational health hazards and use of personal protective equipment among auto mechanics in Kathmandu Metropolitan City, Nepal - Khadka, Rabina; Pandey, Indira; Gautam, Laxmi (International Journal of Occupational Safety and Health, 2021)
Introduction: Auto mechanics are workers who repair and overhaul cars and other automotive vehicles, or their systems and parts. The main objective of the study was to assess knowledge of occupational hazards and the use of safety measures among automobile repair artisans in Kathmandu Metropolitan City. Methods: A cross-sectional study was carried among 400 auto mechanics working garages in Kathmandu Metropolitan City. The data collection was done from May 15th to Jun 13th, 2019. Results: Among the 400 respondents, only 31% had adequate knowledge about occupational hazards due to vehicle repairing. Age, educational status, working hours, years of employment and pre-service training were found to be associated with knowledge on hazards. Two-thirds (63.5%) of the surveyed workers knew the use of PPE and this knowledge was statistically significant with age, educational status, working hours and pre-service training. The study showed that only half (53.5%) of the respondents use one or more PPE during their work despite being exposed to lots of hazards in the working area. Conclusion: Knowledge on health hazards was inadequate. Also, there was a difference in knowledge on PPE and its use. So, there is a need to put the knowledge into practice.